The Korean popular culture reader - Kim, Kyung Hyun, 1969-; Choe, Youngmin (Duke University Press, 2014)
This collection provides a timely and essential foundation for studying Korean popular culture (""K-pop"") by looking at its global popularity, relation to the contemporary cultural landscape, and historical roots